PENGARUH PENYAJIAN LAPORAN KEUANGAN DAERAH DAN AKSESIBILITAS LAPORAN KEUANGAN DAERAH TERHADAP PENGGUNAAN SISTEM INFORMASI PENGELOLAAN KEUANGAN DAERAH - Rohaedi, Andi Nurdin; Sabaruddinsah, Sabaruddinsah (JRAK (Jurnal Riset Akuntansi dan Komputerisasi Akuntansi), 2013)
This study aims to determine the effect of the financial statement presentation and accessibility of thefinancial statements on the use of local financial management information systems in the Departmentof Energy and Mineral Resources of West Java Province. The method used is descriptive quantitative method with causality approach. The population in thisstudy is the internal users of financial statements that direct employees with the preparation offinancial statements in the Department of Energy and Mineral Resources (ESDM) of West JavaProvince. The sampling method use purposive sampling method with the number of respondents 60people. From the research it can be concluded that the financial statements do not affect the use of localfinancial management information system. Furthermore, the accessibility of the financial statementssignificantly influence the use of information systems in the area of financial management of theDepartment of Energy and Mineral Resources of West Java Province